THE COMPARISON BETWEEN THE SECOND MID-TERM ENGLISH TESTS FOR THE SEVENTH GRADERSMADE BY THE STATE AND PRIVATE SCHOOL CERTIFIED ENGLISH TEACHERS (The case of test items analysis of SMP N 1 Semarang and SMP Kesatrian 2 Semarang in the academic year of 2013) - Saputra, Reza Wisnu (ELT Forum: Journal of English Language Teaching, 2015)
One of the teacherâs competencies is the ability in designing a good test. Designing a test is not an easy task to be done. Even for a certified teacher who has already had lot of experiences in teaching and learning process. Through this study, the writer wanted to find out the quality of the second mid-term English tests for the seventh graders made by state and private school certified English teachers. The objective of this study was to compare those tests in term of (1) the validity, (2) the reliability, (3) the item facility, and (4) the item discrimination power. The method used in this study was comparative quantitative research. The tests were takenfrom the teachers of SMP N 1 Semarang as the state school and SMP Kesatrian 2 Semarang as the private school.From the result of the analysis, it was found that the quality of both tests were not good enough. There were 42 items out of 50 items from the mid-term test of SMP N 1 Semarang which did not meet the requirement as a good test. Meanwhile, from the mid-term test of SMP Kesatrian 2 Semarang, there were 38 items out of 50 items which did not meet the requirements as good test. However, from this result, the mid-term test of SMP Kesatrian 2 Semarang was much better than the mid-term test of SMP N 1 Semarang. In conclusion, the qualities of the second mid-term English tests made by the state and private school certified English teachers still need to be revised carefully. Especially, from the view of validity, reliability, item facility, and item discrimination. In addition, from the classification of the item which can be used from those tests, there was a little number of items which can be used.Consequently, the certified English teachers need to improve their knowledge and ability in designing a good test for their students.